2018
DOI: 10.21474/ijar01/6849
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Palm Oil for the Enhancement of Biomass and Polysaccharides Production Through Submerged Fermentation From Locally Isolated Pleurotus Sp. Mycelium.

Abstract: Mushroom is known to be a fungal growth which is in the form of filaments called as hyphae that can only be seen through microscope; with time, these hyphae grow into long network that are known as mycelium [1,2]. Mushrooms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Similar to our study, the C/N ratio was important for the biomass and polysaccharides production from mushroom Pleurotus sp. A C/N ratio of 80:1 yielded enhanced mycelial biomass and IPS and EPS production of 20.1 g/L, 11.89 ± 1.15 mg/mL, and 3.38 ± 1.21 mg/mL, respectively [25].…”
Section: Effect Of Carbon/nitrogen Ratiomentioning
confidence: 97%
See 3 more Smart Citations
“…Similar to our study, the C/N ratio was important for the biomass and polysaccharides production from mushroom Pleurotus sp. A C/N ratio of 80:1 yielded enhanced mycelial biomass and IPS and EPS production of 20.1 g/L, 11.89 ± 1.15 mg/mL, and 3.38 ± 1.21 mg/mL, respectively [25].…”
Section: Effect Of Carbon/nitrogen Ratiomentioning
confidence: 97%
“…mushroom grown in submerged fermentation [25]. It was observed that the maximum mycelium dry weight was observed in the presence of glucose; however, the highest amount of EPS and IPS was obtained in the presence of sucrose [25]. In another study, although sucrose's presence as the carbon source resulted in increased biomass and IPS production from Tuber sinense in submerged fermentation, the maximum EPS was produced in the presence of lactose, even with poor cell growth [23].…”
Section: Effect Of Different Carbon Sources On Mycelial Biomass and P...mentioning
confidence: 98%
See 2 more Smart Citations